Hubungan Tingkat Kedisiplinan Pemakaian Alat Pelindung Mata Dengan Gangguan Kesehatan Mata Pada Pekerja Las Home Industry Di Kartasura - Priyanto, Priyanto, Tarwaka, PGDip, Sc, M. Erg (2016)
Welding workshop is one of the informal work is at risk for accidents and occupational diseases. The use of eye protection is very important for workers, especially to prevent occupational disease or work accident. However, in reality there are many workers who still do not wear it to work. The purpose of this study was to determine the relationship of disicipline level of use eye protective equipment with eye health disorders in home industry welding workers at Kartasura. This type of research is an analytic observational study. The research population are 100 workers, the number of samples studied are 45 respondents with quota sampling technique. Data analysis technique performed with Spearman Rho correlation statistic test. The result showed home industry welding workers are 86.7% rather discipline in the use of eye protection equipment when conducting welding activities. Home industry welding workers in Sub district Kartasura are 53.3% had no eye health disorders. There is a significant correlation (p = 0.000) with a very strong negative correlation (-0.969) between the discipline level of use eye protective equipment with eye health disorders in home industry welding workers at Kartasura.